Experimental study of robotic-based machining. Issue 12 (2016) - Klimchik, A.; Ambiehl, A.; Garnier, S.; Furet, B.; Pashkevich, A.
Abstract: The paper is devoted to the experimental study of robotic based machining for several industrial robots. Particular attention is paid to the robot precision in milling operation and its ability to perform the task with desired accuracy. In contrast to other works, the robot performance is evaluated using the circularity norm that evaluates the contortion of the benchmark circle to be machined. The developed approach is applied to five industrial robots of KUKA family. The validity of the proposed technique was confirmed by experimental study dealing with robot-based machining of circular grooves.